PENGEMBANGAN BAHAN AJAR DAN PENILAIAN OTENTIK MATA KULIAH PENDIDIKAN IPA SEKOLAH DASAR - Purnomo, Heru (Profesi Pendidikan Dasar, 2017)
This study aims to produce teaching materials and assessment of authentic courses of education IPA in Elementary School decent and effective. This research is a research and development. consisting of nine stages, namely: (1) preliminary study, (2) planning, (3) initial product development, (4) initial test, (5) revision to compose the main product, (6) field trial, (7) ) revisions to improve the product of field trial results, (8) field implementation tests, and (9) final product revisions. The results of the study as follows. (1) Feasibility assessment of IPA material experts and science evaluation experts with good criteria with an average rating of 3.8, assessment of IPA materials with an average rating of 4.08, Trial is limited to Good criteria and field implementation trials with good criteria. The effectiveness of product development of gain score calculation know knowledge aspect (knowledge) obtained index of gain equal to 0,71 with High category, Field test result which done in three classes got average result as follows, Student who give Very Good response 27, 2%, good student response with average percentage 54,91%, Student Response with Good enough category 16,27%, while for Student response with Less category equal to 0,66% and Less once 0,99% .